Consumer Decision-Making Creativity and Its Relation to Exploitation–Exploration Activities: Eye-Tracking Approach - Choi, Eunyoung; Kim, Cheong; Lee, Kun Chang (Frontiers in Psychology, 2021)
Modern consumers face a dramatic rise in web-based technological advancements and have trouble making rational and proper decisions when they shop online. When they try to make decisions about products and services, they also feel pressured against time when sorting among all of the unnecessary items in the flood of information available on the web. In this sense, they need to use consumer decision-making creativity (CDMC) to make rational decisions. However, unexplored research questions on this subject remain. Firstly, in what ways do task difficulty and time constraints affect visual attention on exploitative and exploratory activities differently? Secondly, how does the location of the reference (i.e., hints) influence the level of visual attention to exploitative and exploratory activities depending on affordance theory? Thirdly, how do exploratory and exploitative activities affect CDMC? Eye-tracking experiments were conducted with 70 participants to obtain relevant metrics such as TFD (total fixation duration), FC (fixation count), and VC (visit count) to answer these research questions. Our findings suggest that task difficulty influences exploitative activity, while time constraint is related to the exploratory activity. The result of the location of hints aligns with the affordance theory for the exploitative activity. Besides, exploratory activity positively affected CDMC, but exploitative activity did not show any effect.